Fundamental Experiment of a Magnetic Micromachine Capable of Moving in a Liver - WATANABE, Hiroshi; SHOJI, Koichi; SENDOH, Masahiko; ISHIYAMA, Kazushi; SOMA, Munehisa; ARAI, Ken Ichi (Transactions of Japanese Society for Medical and Biological Engineering, 2004)
Magnetic micromachines are driven by magnetic fields and can be operated wirelessly. The devices themselves require no batteries and no controlling parts or machinery. Given these advantages, micromachines are expected to be applied widely in the medical field. As one example, a micromachine equipped with a heating element for hyperthermia and capable of maneuvering within the human body can be used to provide a new cancer therapy for local hyperthermia. In this study, we fabricated a magnetic micromachine capable of moving in the liver, one of the targets of local hyperthermia. The machine consisted of a cutting tip to cut the liver tissue, a cylindrical permanent magnet and a spiral structure made with a tungsten wire. The magnet was magnetized in the direction of its diameter. The machine was designed with a small diameter of only 0.9mm in order to permit the insertion of an 18G injector. When a rotational magnetic field was applied, the magnet rotated and the spiral structure produced thrust force. The micromachine was able to move a distance of 40mm in a porcine liver and 45mm in a bovine liver. These results confirm that the micromachine has excellent potential for medical applications.